2021
DOI: 10.1093/bib/bbab197
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic studies revealed pathophysiological impact of COVID-19 to predominant health conditions

Abstract: Despite the association of prevalent health conditions with coronavirus disease 2019 (COVID-19) severity, the disease-modifying biomolecules and their pathogenetic mechanisms remain unclear. This study aimed to understand the influences of COVID-19 on different comorbidities and vice versa through network-based gene expression analyses. Using the shared dysregulated genes, we identified key genetic determinants and signaling pathways that may involve in their shared pathogenesis. The COVID-19 showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 104 publications
3
10
0
Order By: Relevance
“…TF NRF1 can also target gene TFAM , which encodes TFAM that regulates the homeostasis of mitochondria. Similarly, previous studies have reported that downregulated SIRT1 and PGC1α were observed in COVID-19 patients [ 109 , 110 , 111 ]. We observed the lower expression level of SIRT1, which could be due to the inhibitory effect of MALAT1 [ 112 ].…”
Section: Resultssupporting
confidence: 74%
“…TF NRF1 can also target gene TFAM , which encodes TFAM that regulates the homeostasis of mitochondria. Similarly, previous studies have reported that downregulated SIRT1 and PGC1α were observed in COVID-19 patients [ 109 , 110 , 111 ]. We observed the lower expression level of SIRT1, which could be due to the inhibitory effect of MALAT1 [ 112 ].…”
Section: Resultssupporting
confidence: 74%
“…Additionally, some of the purple module hub-high traffic genes, such as MAPK1 ( 189 , 374 ), CUL2 ( 210 ), CMTM6 ( 162 ), TXNRD1 ( 375 ), RAB1A ( 376 ), DICER1 ( 377 ), RAB5A ( 209 ), HSP90B1 ( 343 ), MAGT1 ( 378 ), ADAM10 ( 379 , 380 ), SNX2 ( 89 ), OLA1 ( 381 ), SPTLC1 ( 382 ), SH3GLB1 ( 383 ), TIMM10B ( 384 ), and CREB1 ( 385 ) hub-high traffic TF, which are central for information exchange in this module, are potential targets for development of COVID-19 therapeutic strategies. Among these, the mitogen-activated protein kinase 1 ( MAPK1 ) hub-high traffic gene is a potential core target for many anti-COVID-19 therapeutic strategies ( 189 , 374 , 386 390 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression profile observed in COVID-19 samples (GSE147507) has similar DEGs as seen with other diseases and comorbidities such as liver cirrhosis, influenza, and colonic neoplasms. These DEGs are also positively regulated in respiratory diseases, arthritis, psoriasis, glioblastoma, Crohn’s disease, ulcerative colitis, colorectal cancer, skin diseases, pneumonia, keratosis, lupus erythematosus, esophageal cancer ( Nain et al., 2021 ). Single-cell transcriptome analyses of colon mucosae of normal, colorectal adenoma (CRA), and colorectal cancer (CRC) patients have shown increased expression of SARS-CoV2 entry-related genes such as ACE2, CD147 (Basigin), TMPRSS2, Cathepsin B (CATB), Cathepsin L (CATL), and Furin.…”
Section: Host Gene Expressions In Liver and Gi Tissue Of Sars-cov2-infected Patientsmentioning
confidence: 99%